2005
DOI: 10.1103/physrevlett.95.227203
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Scattering of Spin Polarized Carriers in(In,Mn)SbDilute Magnetic Semiconductor

Abstract: Magnetoresistance measurements on the magnetic semiconductor (In,Mn)Sb suggest that magnetic scattering in this material is dominated by isolated Mn 2+ ions located outside the ferromagnetically-ordered regions when the system is below Tc. A model is proposed, based on the p-d exchange between spin-polarized charge carriers and localized Mn 2+ ions, which accounts for the observed behavior both below and above the ferromagnetic phase transition. The suggested picture is further verified by high-pressure experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Another point of note is that the measured hole concentration of ϳ10 19 cm −3 for our films is lower than that reported for In 1−x Mn x Sb films grown by LT-MBE of ϳ10 20 cm −3 . [17][18][19] However, the mobility at 300 K of the MOVPE grown films is higher than that of MBE-grown films.…”
Section: B Hall Effect and Magnetic Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Another point of note is that the measured hole concentration of ϳ10 19 cm −3 for our films is lower than that reported for In 1−x Mn x Sb films grown by LT-MBE of ϳ10 20 cm −3 . [17][18][19] However, the mobility at 300 K of the MOVPE grown films is higher than that of MBE-grown films.…”
Section: B Hall Effect and Magnetic Propertiesmentioning
confidence: 91%
“…Magnetotransport studies on InMnSb thin films grown by LT-MBE have been previously reported. 17,18 Initial measurements on In 1−x Mn x Sb films indicate that scattering of carriers by isolated Mn 2+ ions is the dominant mechanism, leading to a negative magnetoresistance for temperatures up to 12 K. 19 These LT-MBE alloys show well-defined magnetic hysteresis loops and an anomalous Hall effect ͑AHE͒. The Curie temperature ͑T C ͒ measured in these samples is very low, on the order of 7-20 K. Recently, however, we have shown that single phase In 1−x Mn x Sb films grown by MOVPE are ferromagnetic at room temperature with a T C in excess of 400 K. 20 Ferromagnetism was supported by field-cooled ͑FC͒ and zero-field-cooled ͑ZFC͒ magnetization measurements and by clear hysteresis in the anomalous Hall resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure has proven to be an effective and clean means to tune the lattice and electron degrees of freedom in topological materials. There have been several reports on pressure tuning of anomalous transports like in dilute magnetic semiconductor (In, Mn)Sb [27][28][29] and MnSi [30]. To the best of our knowledge, the highest pressure achieved is generally smaller than 3 GPa.…”
mentioning
confidence: 99%
“…The magnetoresistance (MR) has been defined as: We observed a well pronounced minimum on the temperature dependence of resistance, R, at about T k ≈ 40K (Fig.3), which should be attributed to Kondo-like behaviour. Few different mechanisms might be considered to explain an increase of the resistivity of a metallic microwire at low temperatures: magnetic Kondo effect, weak localization, enhanced electron-electron interaction, scattering of conduction electrons by structural two-level system (TLS) and scattering of strongly spin-polarized charge carriers on diluted magnetic moments [21][22][23][24]. Figure 3 shows that in the present case the temperature dependence of the resistivity below 40 K has a form typical for the Hamann model [25].…”
Section: Methodsmentioning
confidence: 99%